Efficacy and safety of intravenous vernakalant for the rapid conversion of recent‐onset atrial fibrillation: A meta‐analysis. Issue 3 (4th November 2017) - Akel, Tamer; Lafferty, James
Abstract : Background: Atrial fibrillation is a common cardiac arrhythmia with increasing prevalence in the aging population. It is a major cause of emergency department visits worldwide. Vernakalant, a relatively new antiarrhythmic drug with selectively preferential effects on the atrial tissue is currently used in many European countries for the termination of recent‐onset atrial fibrillation. Presently, the drug is still not approved by the United States Food and Drug Administration due to safety concerns. We evaluate the efficacy and safety of vernakalant for the conversion of recent‐onset atrial fibrillation or atrial flutter into normal sinus rhythm (NSR). Methods: PubMed/MEDLINE (1993–2017), the Cochrane Central Register of Controlled Trials (2000–2017), and reference lists of relevant articles were searched for randomized controlled trials (RCTs) comparing vernakalant to a control drug and extracted subsequently. Results: Nine RCTs were identified and included in the meta‐analysis. Pooled analysis of events extracted for a total of 1421 patients with recent‐onset atrial fibrillation showed a statistically significant increase in cardioversion within 90 minutes from drug infusion (Relative Risk [RR], 6.61; 95% Confidence Interval [CI], 2.78 – 15.71; p  < .00001). In terms of adverse events, vernakalant was considered safe in comparison to control drugs (RR, 0.80; 95% CI, 0.61–1.05; p  = .11). Conclusion: Vernakalant is effective for rapid conversion of recent‐onset atrial fibrillation into NSR. However, although it showed a safe profile in terms of side effects in this analysis, we are still hesitant about this conclusion and few safety issues should be addressed within specific patients' subgroups.